Identification of two interacting quantitative trait loci controlling for condensed tannin in sorghum grain and grain quality analysis of a sorghum diverse collection - Xiang, Wenwen (Kansas State University, 2009)
Tannin, a second metabolic product in sorghum, has been directly related to resistance to insects and birds. Tannin also impacts sorghum nutritional value. Previous studies have shown tannin content has a positive correlation with early season cold tolerance, an important agronomic trait. Sorghum contains condensed tannins in testa layer below the pericarp. The testa layer tannin is controlled by two complementary genes B1 and B2: tannins are present when both genes are dominant but absent when only one or none of these two is dominant. The purpose of this research is to identify and map QTLs associated with the presence of condensed tannins, analyze interaction of QTLs, and provide a potential path to dissect the more complex trait of early season cold tolerance in future studies. A population of 109 F6:7 recombinant inbred lines (RILs) developed from the cross of a high tannin sorghum Shan Qui Red (SQR) and non-tannin line Tx430 was used in the mapping study. Two QTLs related to condense tannin presence in testa layer were mapped to chromosome 2 and 4, respectively. Strong epistatic interaction of these two QTLs was detected. The two QTLs together with their interaction explained 74% of the phenotypic variation. Sorghum grain quality traits, including kernel size, kernel hardness, protein and starch content, are complex traits which are directly related to sorghum nutritional value and market value. Association mapping is a promising method for complex quantitative traits analysis and dissection in plant science. Sorghum grain quality trait association analysis research is purposed to analyze large amount of grain quality data based on a diversity panel. A sorghum bicolor panel of 300 lines including germplasm derived from sorghum conversion program and elite commercial lines were established and served as diversity population for the association study. Phenotypic data of grain quality traits were collected by single kernel characterization system (SKCS) and near infrared reflectance spectroscopy (NIRS). Data analysis proved high diversity within the SB panel. A correlation between tannin presence and kernel hardness was also observed. Quality traits showed high consistence across years and environments.
Keywords: Grain Quality; QTL; Epistasis; Sorghum; Agriculture, Agronomy (0285); Biology, Genetics (0369)